2002
DOI: 10.1021/jf0256541
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selenium Species in Brazil Nuts by HPLC−ICP-MS and ES-MS

Abstract: Brazil nuts have been classified as the foodstuffs that contain the highest level of unadulterated selenium, an essential trace element that appears to prevent cancer. To date, characterization of the selenium species in brazil nuts has not yet been investigated. In this work, various sample preparation approaches, including microwave extractions and enzymatic treatments, are examined with the goal of species preservation and subsequent selenium speciation; of these approaches, an enzymatic treatment with Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 27 publications
4
69
1
8
Order By: Relevance
“…KBH 4 (Tianjin Refined Chemical Institution, China) and KOH (Acros, USA) were of analytical grade. 1.5% (w/v) KBH 4 was prepared in 0.2% (w/v) KOH solution.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…KBH 4 (Tianjin Refined Chemical Institution, China) and KOH (Acros, USA) were of analytical grade. 1.5% (w/v) KBH 4 was prepared in 0.2% (w/v) KOH solution.…”
Section: Chemicalsmentioning
confidence: 99%
“…Only one UV cracker supplied by the manufacturer was utilized to realize the transformation of all selenium species. No other reductant except HCl and KBH 4 were added. The simplification of the hyphenation equipment reduced the peak breadth effectively and gave symmetric and sharp chromatographic peaks.…”
Section: Optimization Of Uv Irradiation and Hydride Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Caruso and co-workers 18 studied the distribution of various elements of nutritional and toxicological interest in different molecular weight fractions, ranging from 0.18 to 14 kDa. Chemical speciation has been accomplished for As and Se in Brazilnut [20][21][22] and Ni, Cu, Zn and Mn in different edible nuts. 19,23 Cupuassu (Theobroma grandiflorum) has a whiteyellow pulp with pleasant acidic taste and a strong fragrance, which is widely consumed as juice, ice cream and jam.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In fact, studies have shown that selenium in the form of seleno-amino acids is more easily absorbed by the body than inorganic forms. 9 The scientific community has shown increasing interest in the determination of the elemental composition of milk, because of its important role in human health. 10,11 The concentration of selenium in milk has been reported to vary by geographical region, and depends on factors such as selenium levels in soil and water, as well as in local plants and food.…”
Section: Introductionmentioning
confidence: 99%